Optimal timing of policy interventions in troubled banks - König, Philipp J.; Mayer, Paul; Pothier, David (Journal of Financial Intermediation, 2024)
When will a policy authority (PA) resolve a bank whose solvency is uncertain? Delaying resolution gives the PA time to obtain information about the bank’s solvency. Delaying resolution also gives creditors time to withdraw funds, raising the cost of bailing out depositors. The optimal resolution date trades off these costs with the option value of making a more efficient resolution decision given new information. Providing liquidity support buys the PA time to wait for information, but increases its losses if the bank turns out to be insolvent. The PA may therefore optimally delay the provision of liquidity support.